Parrhesia, the scream and the cracks: epitomes of emancipatory decolonial languages - Estefogo, Francisco (The ESPecialist, 2024)
This essay aims to reflect on the perspectives of emancipatory decolonial languages in favor of multi- and intercultural education (Walsh, 2009, 2019), so that educational activity is understood as an alethurgical political task (Foucault, 1996, 2011). In other words, an educational practice that transgresses protocols, with a view to ethical and critical participatory citizen action, as a builder of new realities and ways of being, living, desiring and thinking, therefore, questioning the status quo and providing care for oneself and on the other (Foucault, 1996, 2011). Through parrhesia (Foucault, 1996, 2011) and, strictly speaking, screams and cracks (Walsh, 2009, 2019), the focus of this proposal is to debate cultural diversities, be they linguistic, political, social, ethnic, cultural, religious or gender-based, as epistemic decolonial pedagogical capital (Mignolo, 2017; Quijano, 2005; Walsh, 2009, 2019). Likewise, as a characteristic and immanent vocation of humanity for ontological, epistemological, ethical-political advancement, and, therefore, a possible source of emancipatory decolonial languages.